Experimental cell models of insulin resistance: overview and appraisal - Yang, Ying; Wang, Ting-ting; Xie, Hu-ai; Hu, Ping Ping; Li, Pan (Frontiers in Endocrinology, 2024)
Insulin resistance, a key factor in the development of type 2 diabetes mellitus (T2DM), is defined as a defect in insulin-mediated control of glucose metabolism in tissues such as liver, fat and muscle. Insulin resistance is a driving force behind various metabolic diseases, such as T2DM, hyperlipidemia, hypertension, coronary heart disease and fatty liver. Therefore, improving insulin sensitivity can be considered as an effective strategy for the prevention and treatment of these complex metabolic diseases. Cell-based models are extensively employed for the study of pathological mechanisms and drug screening, particularly in relation to insulin resistance in T2DM. Currently, numerous methods are available for the establishment of in vitro insulin resistance models, a comprehensive review of these models is required and can serve as an excellent introduction or understanding for researchers undertaking studies in this filed. This review examines and discusses the primary methods for establishing and evaluating insulin resistance cell models. Furthermore, it highlights key issues and suggestions on cell selection, establishment, evaluation and drug screening of insulin resistance, thereby providing valuable references for the future research efforts.